Peniadaan Pidana Penjara bagi Pelaku Lansia dalam Pembaruan Hukum Pidana, Dapatkah Keadilan Restoratif Tercapai? (Elimination of Imprisonment for Erderly Criminal Offenders in Criminal Law Reform, Can Restorative Justice Be Achieved?) - Puteri Hikmawati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2020)
The Criminal Code Bill which has been approved by the House of Representatives and the Government, but has been delayed on its legalization, contains provisions to eliminate imprisonment for elderly over 75 years. Protection of the elderly is a human right because it belongs to vulnerable groups, such as children. For children in conflict with the law, restorative justice has been applied with diversion, where a solution is sought by involving the offenders, victims and the community. This article is written with normative juridical research method that examines the elimination of imprisonment for elderly criminal offenders in criminal law reform; with a question on achievability of restorative justice, which is expected to enrich criminal law extensive knowledge. This issue is important because the Criminal Code has not yet regulated the protection of elderly criminal offenders. Based on the results of the study, the judge was given an alternative sentence to impose a criminal fine to the elderly as a substitute for imprisonment, with due regard to the objectives and guidelines for punishment, as well as under strict conditions. Thus, restorative justice for elderly criminal offenders can't be achieved. The application of restorative justice should be carried out with regard to the rights of victims to obtain compensation. Therefore, there is a need for readiness of laws and regulations, law enforcement officers, and the community. The community needs to be given an understanding that, children and the elderly are vulnerable groups, and their rights are guaranteed by the 1945 Constitution. With age as their major factor, elderly are exposed to social, economic and health limitations. AbstrakRUU KUHP yang telah disetujui oleh DPR dan Pemerintah, namun ditunda pengesahannya memuat ketentuan untuk sedapat mungkin tidak menjatuhkan pidana penjara bagi lansia di atas usia 75 tahun. Pelindungan terhadap lansia merupakan hak asasi manusia karena termasuk dalam kelompok rentan, seperti halnya anak. Terhadap anak yang berhadapan dengan hukum telah diterapkan keadilan restoratif dengan diversi, dimana diupayakan penyelesaian dengan melibatkan pelaku, korban, dan masyarakat. Penulisan artikel dengan metode penelitian yuridis normatif ini mengkaji peniadaan pidana penjara bagi pelaku lansia dalam pembaruan hukum pidana, dapatkah keadilan restoratif tercapai?, yang diharapkan dapat menambah khasanah ilmu pengetahuan hukum pidana. Hal ini penting, mengingat KUHP belum mengatur pelindungan terhadap pelaku tindak pidana lansia. Berdasarkan hasil kajian, hakim diberikan alternatif pemidanaan untuk menjatuhkan pidana denda bagi lansia sebagai pengganti pidana penjara, dengan memperhatikan tujuan dan pedoman pemidanaan, serta syarat-syarat yang ketat. Dengan demikian, keadilan restoratif bagi pelaku lansia, tidak dapat tercapai. Penerapan keadilan restoratif hendaknya dilakukan dengan memperhatikan hak korban untuk memperoleh ganti rugi. Oleh karena itu, perlu kesiapan peraturan perundang-undangan, aparat penegak hukum, dan masyarakat. Terhadap masyarakat perlu diberikan pemahaman bahwa, anak dan lansia merupakan kelompok rentan, yang haknya dijamin oleh UUD 1945. Seorang lansia karena faktor usianya menghadapi keterbatasan sosial, ekonomi, dan kesehatan.